(untitled) (Transport systems and technologies, 2021)
Comparative analysis of main requirements of the technical regulations concerning conformity assessment of the movable pressure equipment is given in the article. Terms, used in the technical regulations are considered, similarity and divergence of requirements is analyzed, classification of dangerous goods, examples of liabilities of the assessment process participants, appointed bodies concerning their activities is given.